ANALISIS GAMBAR KARYA ANAK USIA DINI BERDASARKAN TEORI PERKEMBANGAN SENI RUPA ANAK VIKTOR - Sindu Putra, Ida Bagus Komang (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
This research will be a descriptive study with qualitative data analysis about Early childhood’s drawing according to Children’s art development by Victor. The objectives of this study include; (1) to find out the visual element of early childhood’s drawing (2) to find out the aesthetic value of early childhood’s drawing. (3) to find out early childhood’s drawing according to children’s art development theory by Victor. The data collection techniques in this study include; (1) observation, (2) Interview, (3) Documentation, with qualitative and quantitative data analysis of Mile and Huberman which includes; (1) Data reduction, (2) Data presentation, and (3) Conclusion.